A preliminary laboratory study of motion of floating debris generated by solitary waves running up a beach - Shen, Hung-Tao (2014)
Destructive tsunamis can destroy coastal structures and move huge amounts of tsunami debris. Our current understanding of motion of tsunami debris in tsunami flows is limited. In this paper, we present a preliminary laboratory study of motion of model debris under the action of solitary waves running up a beach. The difference between the waterline of maximum inundation and the final position of debris was examined under various conditions. Effects of solitary wave height, water depth, and the distance of debris source to the shoreline on the maximum inundation, the debris limit, and the final position of debris were examined. In general, the final positions of the debris are different from the waterline at maximum inundation and there is a low possibility that a large amount of debris can be carried by retreating water offshore into the sea.